Vaginal Microbiota during Estrous Cycle and its Plausible Association with Certain Hematological Parameters in Bubalus bubalis - Mahesh, P; suthar, VS; Patil, DB; Joshi, Madhavi; Joshi, CG; Bagatharia, SB (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The study on the dynamics of vaginal microbiota during the estrous cycle and its plausible association with certain hematological parameters in Bubalus bubalis was conducted on nine buffalo heifers at a private dairy farm. Out of nine, eight heifers responded to the synchronization protocol and included in the experiment. Blood collection using vacutainers and vaginal flushing using sterile normal saline with a syringe and AI sheath was carried out on ‘0’ (estrus), 4th (metestrus), 9th (diestrus) and 19th day (proestrus) of the synchronized estrous cycle. The collected vaginal samples were lyophilized, DNA isolated using Qiagen stool kit, and amplified with fusion primer for Bacteria (16S rRNA), Fungi (ITS 6-8), and Archaea (16S rRNA). The amplicon library constructed was sequenced through Ion PGM machine and annotation was carried out through MG-RAST with rRNA database SILVA ssu with 98% identity. The results revealed four major domains - Bacteria (93.8%), Eukaryota (5.7%), Archaea (0.006%), and Unclassified sequences (0.41%). A total of 2196 bacterial species, 17 fungal species, and two archaeal species were detected confirming the richest diversity of vaginal microflora in buffalo heifers. The highly abundant domain-bacteria contained 18 bacterial phyla and were grouped into four high (>5%), six moderate (0.1- 5%), and eight less abundant groups (0-0.1%). The results of hematological parameters were within the normal range. There was no impact of four stages of the estrous cycle on hematological parameters studied and no associations of bacterial phyla with them. Out of a total of 588 bacterial genera, only 14 showed a negative association, while four genera showed a positive association with blood monocytes. Similarly, only Moraxella, Microcoleus, Thiomonas showed negative associations with WBC, lymphocyte, and granulocyte, and Weissella genus showed a negative association with lymphocyte. No association was observed between types of white blood cells and fungus or archaea. These results of association of vaginal microflora with hematological parameters may be of unknown reasons and suggest further investigations.